PERSEPSI AKUNTAN PENDIDIK TERHADAP PENTINGNYA PENERAPAN AKUNTANSI SOSIAL PADA SUATU PERUSAHAAN - Bambang Widarno, Delvi Safira Salawati, Rispantyo & (Universitas Slamet Riyadi, 2017)
The aims of this research is to know how the effects of government regulation,public pressure, environmental organization pressure, and media pressure on theimportance of application social accounting to the company. In addition, to know thedifference of perceptions among the accountant fellow educators about theimportance of social accounting application at the company. This research is aquantitative with population research of the accountant educators in College. Thesampling is already done by convenience sampling method which is based onconvenience and criteria that is accredited Higher Education (College) in Surakartawith A and B accreditation, there is UNIBA, UMS and UNSA. And lecturers whoteach more than five (5) years. The techniques of data collection is using questionerwith 5 point of Likert scale. The technique of data analysis is using test instrumentresearch consist of validity test and reliability test, classical assumption test consistof multicolinearity test, heteroskedastisitas test, autokorelas testi, and normality test,multiple linear regression test, hypothesis test and difference perception test. Theresult shows the government regulation, public pressure, environmental organizationpressure, and media pressure have a positive influence and significant on theapplication of social accounting in the company. In addition, there is not differenceperceptions between male and female accountant educators about the application ofsocial accounting in the company.Keywords: Perception of Accountant Educators, Social Accounting, SocialAccountability Accounting, Social Accounting Implementation.